Ozone Amplifies Water Loss from Mature Trees in the Short Term But Decreases It in the Long Term - Elena Paoletti (Forests, 2019)
We measured whole-tree transpiration of mature Fagus sylvatica and Picea abies trees exposed to ambient and twice-ambient O3 regimes (1xO3 and 2xO3 free-air fumigation). After eight years, mean daily total transpiration did not vary with the O3 regime over the 31 days of our study, even though individual daily values increased with increasing daily O3 peaks in both species. Although the environmental parameters were similar at 1xO3 and 2xO3, the main factors affecting daily transpiration were vapour pressure deficit in 2xO3 spruce and O3 peaks in beech. For a mechanistic explanation, we measured O3-induced sluggish stomatal responses to variable light (sunflecks) by means of leaf-level gas exchange measurements only in the species where O3 was a significant factor for transpiration, i.e., beech. Stomata were always slower in closing than in opening. The 2xO3 stomata were slower in opening and mostly in closing than 1xO3 stomata, so that O3 uptake and water loss were amplified before a steady state was reached. Such delay in the stomatal reaction suggests caution when assessing stomatal conductance under O3 pollution, because recording gas exchange at the time photosynthesis reached an equilibrium resulted in a significant overestimation of stomatal conductance when stomata were closing (ab. 90% at 1xO3 and 250% at 2xO3). Sun and shade leaves showed similar sluggish responses, thus suggesting that sluggishness may occur within the entire crown. The fact that total transpiration was similar at 1xO3 and 2xO3, however, suggests that the higher water loss due to stomatal sluggishness was offset by lower steady-state stomatal conductance at 2xO3. In conclusion, O3 exposure amplified short-term water loss from mature beech trees by slowing stomatal dynamics, while decreased long-term water loss because of lower steady-state stomatal conductance. Over the short term of this experiment, the two responses offset each other and no effect on total transpiration was observed.